1991
DOI: 10.1152/ajpheart.1991.261.3.h656
|View full text |Cite
|
Sign up to set email alerts
|

Modulation by extracellular pH of bradykinin-evoked activation of Ca(2+)-activated K+ channels in endothelial cells

Abstract: We used the patch-clamp technique to investigate, via the activation of Ca(2+)-activated potassium channels [K(Ca2+)channels], the effects of extracellular pH (pHo) on the bradykinin (BK)-stimulated rise in cytosolic Ca2+ concentration in bovine aortic endothelial cells (BAE). In cell-attached experiments, the external application of BK caused a transient activation of the K(Ca2+) channels. Increasing pHo from 7.3 to 9 maintained the channel activity, which was not inhibited by withdrawing the agonist. The cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1992
1992
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…They show Ca 2+ -and voltage-dependent activation and are blocked by TEA, charybdotoxin, d-tubocurarine (8,30,147), and by extracellular alkalinization (170). The NO-releaser LP-805 (72) potentiates outward Ca 2+ -dependent K + currents in bovine pulmonary artery ECs, but it is not clear whether this effect is direct or mediated by changes in [Ca 2+ ] i .…”
Section: Potassium Channelsmentioning
confidence: 99%
“…They show Ca 2+ -and voltage-dependent activation and are blocked by TEA, charybdotoxin, d-tubocurarine (8,30,147), and by extracellular alkalinization (170). The NO-releaser LP-805 (72) potentiates outward Ca 2+ -dependent K + currents in bovine pulmonary artery ECs, but it is not clear whether this effect is direct or mediated by changes in [Ca 2+ ] i .…”
Section: Potassium Channelsmentioning
confidence: 99%
“…Intracellular alkalinization, however, is strictly dependent on the presence of extracellular sodium and sensitive to inhibition by amiloride analogs (46,47); as such, it can be attributed to activation of the Na + -H + exchanger. Experimental evidence has suggested that exchanger activation is linked to both the release of Ca 2+ from intracellular stores and the agonist-induced transmembranous Ca 2+ influx (48). Indeed, a number of studies have linked changes in pH t with alterations in [Ca 2+ ]i.…”
Section: Kinin-mediated Cell Signalingmentioning
confidence: 99%
“…For example, maintained intracellular alkalinization induced by either NH 4 + or methylamine has been reported to empty intracellular Ca 2+ stores without stimulating IP 3 formation (42). Although, in the absence of an agonist, intracellular alkalinization has not been associated with a significant increase in K + channel activity, an increased endothelial pHj has been shown to enhance bradykinin-induced activation of Kc a 2+ channels and prolong the transmembranous Ca 2+ influx (42,48). These data indicate that the agonist-evoked Ca 2+ entry pathway responsible for the refilling of intracellular Ca 2+ stores may be modulated by changes in pHj.…”
Section: Kinin-mediated Cell Signalingmentioning
confidence: 99%
“…Up to now, only a few studies have addressed the question of how Ca# + entry into vascular endothelial cells is promoted during extracellular alkalosis. Alkalosis (pH o 8.5) was reported to augment Ca# + influx into store-depleted endothelial cells [19,20]. Since Ca# + influx into activated cells generally comprises the background leak Ca# + influx and the Ca# + influx occurring via activated Ca# + channels, the relative contribution of pH modulation of either component to the overall effect is still unclear.…”
Section: Introductionmentioning
confidence: 99%